Removal of Tetracycline from Wastewater Using Circulating Fluidized Bed - Kareem, Sabreen Lateef; Mohammed, Ahmed A (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
In this study, the circulating fluidized bed was used to remove the Tetracycline from wastewater utilizing a pistachio shell coated with ZnO nanoparticles. Several parameters including, Tetracycline solution flowrate, initial static bed height, Tetracycline initial concentration and airflow rate were systematically examined to show their effect on the breakthrough curve and the required time to reach the adsorption capacity and thus draw the fully saturated curve of the adsorbent. Results showed that using ZnO nanoparticles will increase the adsorbent surface area and pores and as a result the adsorption increased, also the required time for adsorbent saturation increased and thus the removal efficiency may be achieved at minimum antibiotic flowrate, maximum bed height, higher antibiotic concentration, and higher airflow rate. Also, a minimum fluidization velocity correlation was developed in this study. This correlation was found to be a function of liquid velocity, bed height, particle size, and particle density. The results showed that circulating fluidized bed has a better performance and last more than two hours before the bed biomass exhausted in comparison with traditional fluidized bed.